Neuromedins NMU and NMS: An Updated Overview of Their Functions - Malendowicz, Ludwik K.; Rucinski, Marcin (Frontiers in Endocrinology, 2021)
More than 35 years have passed since the identification of neuromedin U (NMU). Dozens of publications have been devoted to its physiological role in the organism, which have provided insight into its occurrence in the body, its synthesis and mechanism of action at the cellular level. Two G protein-coupled receptors (GPCRs) have been identified, with NMUR1 distributed mainly peripherally and NMUR2 predominantly centrally. Recognition of the role of NMU in the control of energy homeostasis of the body has greatly increased interest in this neuromedin. In 2005 a second, structurally related peptide, neuromedin S (NMS) was identified. The expression of NMS is more restricted, it is predominantly found in the central nervous system. In recent years, further peptides related to NMU and NMS have been identified. These are neuromedin U precursor related peptide (NURP) and neuromedin S precursor related peptide (NSRP), which also exert biological effects without acting via NMUR1, or NMUR2. This observation suggests the presence of another, as yet unrecognized receptor. Another unresolved issue within the NMU/NMS system is the differences in the effects of various NMU isoforms on diverse cell lines. It seems that development of highly specific NMUR1 and NMUR2 receptor antagonists would allow for a more detailed understanding of the mechanisms of action of NMU/NMS and related peptides in the body. They could form the basis for attempts to use such compounds in the treatment of disorders, for example, metabolic disorders, circadian rhythm, stress, etc.